Kontaminasi Telur Ascaris Lumbricoides Pada Daun Selada (Lactuca Sativa) Di Burger Bundaran Pa’baeng-Baeng Kota Makassar - Kasim, Khiki Purnawati; Rostina, Rostina; Julianti , Putri Dwi (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Roundabout burgers are a recommendation for a burger snack that is popular in Makassar which uses lettuce leaves as a complement. The growing conditions of lettuce leaves pose a risk of contamination by Ascaris lumbricoides worm eggs if humans touch them with dirty hands, washing and processing methods are not correct so that the worm eggs still stick to the lettuce. The aim of this research is to determine the contamination of worm eggs on lettuce leaves and to determine the process of washing, storing and serving lettuce leaves at the Makassar City Pa'Baeng-baeng roundabout burger. This research method is observational with a descriptive approach, and laboratory examination. The samples in this study were lettuce leaves from 14 burger carts at the Pa'baeng-baeng burger roundabout in Makassar City. The results showed that of the 14 lettuce samples, all samples were positively contaminated with Ascaris lumbricoides worm eggs. In the observation results of washing lettuce leaves, all traders did not meet the requirements, while during the storage process 11 traders did not meet the requirements and during the serving process there were 4 traders who did not meet the requirements. The conclusion obtained from the research that has been carried out is that all 14 lettuce leaf samples were positively contaminated with Ascaris lumbricoides worm eggs and there were still carts carrying out washing, storage and serving processes that did not meet the requirements. It is recommended that burger traders wash lettuce leaves with running water and have closed storage shelves.